Audit Operasional Pelayanan Pada PT. XYZ Dengan Menggunakan Kerangka Kerja ITIL Service Operation - Loisa, Julia; Christianto, Kevin; F. Andry, Johanes (Institut Teknologi dan Bisnis Kalbis, 2019)
This research was investigated to conduct an audit operational IT service management. Service has become a special key in forming a good organizational environment, there have been many studies that prove that a good level of service is directly proportional to loyalty, productivity, etc. from end users. In this study focused on the operational processes of the information system services provided by the company to all stakeholders of the information system users, because the operational side is the spearhead of the service process that is reached by stakeholders. The researcher conducted a literature study, interviews, observations, questionnaires, examined documents and analyzed the results of questionnaires and document checks to obtain factual data from the field which would later be used as risk analysis and recommendations for solutions to be provided by researchers. The researcher himself uses the ITIL v3 framework which focuses on the Service Operation which will be matched with the information system service commitments contained in the Service Level Agreement.